Graphene-based photocatalysts for organic pollutant removal from waste-water: recent progress and future challenges. Issue 1 (1st January 2021) - Sabir, Rabia; Waheed, Ammara; Moazzam Ali, Muhammad; Mushtaq, Umar
ABSTRACT : Graphene (G), a two-dimensional carbon layer, is regarded as twenty-first century wonder material and due to its remarkable physio-chemical properties it has been explored for application in various science and technology areas. In environmental remediation field, the quest for eco-friendly and green processes has put a growing emphasis on solar-driven photocatalysis. The conventional semiconductor photocatalysts suffer with the shortcoming of electron–hole pair recombination, aggregation and wide band gap, which inhibit their commercialization. Coupling of graphene derivatives, such as graphene oxide (GO) and reduced graphene oxide (RGO), with semiconductors (TiO2, ZnO) offers a considerable potential to enhance the photocatalytic efficiency by providing higher surface area, stability, and fast electron conduction ability. Numerous papers have been published in recent years which couples Graphene, GO and RGO with different semiconductors for photocatalytic degradation of various organic pollutants. So, it is high time a comprehensive review should be presented to understand the potential and future prospects of photocatalysis in water treatment. This article aims to provide a critical review about recent progress in fabrication methods, modification techniques (non-metal or metal doping), efficiency and mechanism for organic pollutant photo degradation and visible light activation of graphene-based photocatalysts. The role of graphene in photocatalysis and organic pollutant degradation mechanism is summarized. Moreover, novel graphene and layered double hydroxide (LDH) composites are also discussed as potential candidates in wastewater treatment. Furthermore, future prospects and challenges such as separation, recyclability and health hazards of these composites are discussed to provide an outlook about their practical application in water purification. GRAPHICAL ABSTRACT: UF0001